Destructive processing by asparagine endopeptidase limits presentation of a dominant T cell epitope in MBP. - Manoury, B; Mazzeo, D; Fugger, L; Viner, N; Ponsford, M; Streeter, H; Mazza, G; Wraith, D; Watts, C (2002)
Little is known about the processing of putative human autoantigens and why tolerance is established to some T cell epitopes but not others. Here we show that a principal human HLA-DR2-restricted epitope--amino acids 85-99 of myelin basic protein, MBP(85-99)--contains a processing site for the cysteine protease asparagine endopeptidase (AEP). Presentation of this epitope by human antigen-presenting cells is inversely proportional to the amount of cellular AEP activity: inhibition of AEP in living cells greatly enhances presentation of the MBP(85-99) epitope, whereas overexpression of AEP diminishes presentation. These results indicate that central tolerance to this encephalitogenic MBP epitope may not be established because destructive processing limits its display in the thymus. Consistent with this hypothesis, AEP is expressed abundantly in thymic antigen-presenting cells.